Developing and validating the construct maps to assess mathematical proficiencies - Tachamaporn Saikang; Putcharee Junpeng; Nuchwana Luanganggoon; Samruan Chiajunthuk; Prapawadee Suwannatrai; Metta Marwiang; Keow Ngang Tang; Mark Wilson (International Journal of Evaluation and Research in Education (IJERE), 2024)
The study was aimed to develop and validate a measurement test to assess mathematical proficiencies in the numbers and algebra strand. A total of 125 seventh-grade learners with diverse learning abilities from secondary educational institutions under the management of the Khon Kaen Educational Service Area 25, Thailand was chosen as respondents. The researchers employed design-based research consisting of four building blocks to construct a prototype utilizing a construct modeling approach. Firstly, the researchers developed construct maps to identify the learners’ mathematical proficiency (MP) level. This was followed by the creation of the items of measurement test according to the proficiency levels. Next, the researchers allocated scoring measures and formed the conversion of learners’ MP stages. Lastly, the researchers validated the superiority of the measurement test through Wright map consuming the multi-dimensional random coefficient multinomial logit model. The construct maps of the MP level consisted of two dimensions, namely mathematical procedures and structure of learning outcome. Findings discovered that there were 20 items in the assessment tool and its quality passed the determined education and psychological assessment criteria. It can be determined that every item is capable to measure the learners’ multi-dimensional mathematical proficiencies.